The importance of masticatory functional analysis in the diagnostic finding and treatment planning for prosthodontic rehabilitation - Harry Laksono; Agus Dahlan; Sonya Harwasih (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: The masticatory system as a biologic system is subjected to harmful influences of varying severity. Almost half of routine patients requesting prosthodontic treatment indicated at least one sign or symptom of temporomandibular disorders. Analysis of the masticatory system often neglected by dentist. Untreated temporomandibular disorders may significantly implicated in the perpetuation of the disorder and may interfere with routine prosthodontic clinical procedures. It would be resulted unsuccessful long term goal of prosthodontic rehabilitation because of the uncompleted diagnoses and treatment plan. Purpose: The purpose of this case report was to give the information of the importance of masticatory functional analysis in the diagnostic finding for treatment planning in the prosthodontic rehabilitation. Case: A 45 year - old male patient, partial dentate with reduced chewing efficiency, mild pain in right preauricular region in function, left click in opening mouth, severe attrition on all anterior lower teeth with vertical dimension of occlusion decreased due to loss of posterior support. He wanted to make a new denture. Case management: Record and analyze of active and passive mandibular movement, opening pathway, muscle and temporomandibular joints palpation, load testing, and vertical dimension of occlusion with manual functional analysis (MFA), occlusal condition and radiographic examination. Treatment plan was formulated into 3 phases: stabilization of the masticatory system, definitive treatment and periodical control. The result of this treatment excellent for 1 year evaluation after permanent cementation. Conclusion: Masticatory functional analysis is very important and must be done in the diagnosis finding for treatment planning in every case of prosthodontic rehabilitation.Latar belakang: Sistem pengunyahan sebagai sistem biologis sewaktu-waktu dapat terjadi gangguan dengan berbagai derajat keparahan. Hampir setengah dari jumlah pasien yang memerlukan perawatan prostodontik minimal menunjukkan satu tanda atau keluhan dari gangguan temporomandibular. Analisis fungsional sistem pengunyahan masih sering dilupakan oleh dokter gigi. Gangguan temporomandibular yang tidak dirawat akan terus ada dan mungkin dapat mengganggu prosedur klinis perawatan prostodonsia. Hal tersebut akan menyebabkan keberhasilan klinis jangka panjang perawatan prostodonsia tidak dapat tercapai karena diagnosis dan rencana perawatan yang kurang lengkap. Tujuan: Tujuan dari laporan kasus ini adalah untuk memberikan informasi tentang pentingnya analisis fungsional sistem pengunyahan untuk menegakkan diagnosis dan rencana perawatan pada perawatan prostodonsia. Kasus: Pasien laki-laki usia 45 tahun, bergigi sebagian merasa sulit untuk mengunyah makanan, nyeri ringan di daerah depan telinga kanan saat fungsi, keletuk sendi kiri saat membuka mulut, atrisi pada seluruh gigi depan rahang bawah disertai penurunan dimensi vertikal oklusi akibat kehilangan dukungan gigi belakang. Dia ingin membuat gigi tiruan yang baru. Tatalaksana kasus: Mencatat dan menganalisis pergerakan aktif dan pasif rahang bawah, arah pergerakan rahang bawah saat membuka mulut, palpasi otot-otot pengunyahan dan sendi temporomandibula, uji beban, dimensi vertikal oklusi dengan metode analisis fungsional secara manual, keadaan oklusal dan radiologis. Rencana perawatan dibagi menjadi 3 tahap berupa stabilisasi sistem pengunyahan, perawatan tetap dan kontrol secara periodik. Hasil perawatan menunjukkan keberhasilan klinis yang baik setelah dilakukan evaluasi selama 1 tahun setelah penyemenan tetap. Kesimpulan: Analisis fungsional sistem pengunyahan sangat penting dan harus dilakukan untuk menegakkan diagnosis dan rencana perawatan pada setiap perawatan prostodonsia.